Sabelo Ndlovu-Gatsheni and African decolonial studies - Falola, Toyin, author.
1 online resource.
Keywords: "This book considers the work of the preeminent scholar on decoloniality, Sabelo Ndlovu-Gatsheni, as a means of examining the development of decoloniality discourse and of considering the future direction of the African knowledge economy. Sabelo Ndlovu-Gatsheni has been instrumental in the construction of theories and ideas necessary for advancing a decolonial system of education and epistemology. This book considers how Professor Ndlovu-Gatsheni's work has helped to shape our thinking both on Mugabe and the history of Zimbabwe, and beyond to the broader questions of race, liberation, higher education, and the future of decolonial studies. Renowned author Professor Toyin Falola then invites us to consider the dangers of continued repression of African epistemologies, and the enormous benefits of an alternative knowledge economy in which a diverse multiplicity of ideas drives our understanding of the world on to new heights. Unpacking the various conceptual leanings of decoloniality through the works of one of its leading lights, this book will be an essential read for researchers across the fields of African Studies, Race Studies, Philosophy, and Education"--